2021
DOI: 10.3390/ijerph18083998
|View full text |Cite
|
Sign up to set email alerts
|

Economic Crisis: A Factor for the Delayed Diagnosis of Breast Cancer

Abstract: Considering the constant increase in breast cancer patients, identifying factors that influence the moment of diagnosis is essential for optimizing therapeutic management and associated cost. The purpose of the study is to evaluate the impact of the economic crisis on the moment of a breast cancer diagnosis. This retrospective observational study analyzed a cohort of 4929 patients diagnosed with breast cancer over the course of 19 years in the Western region of Romania. The time interval was divided based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Similarly, a study in Romania (12) revealed a significantly higher percentage of patients diagnosed with late-stage breast cancer during the country's economic crisis compared to the previous interval (56.3% vs. 46.9%). These findings are in accordance with the international literature, which supports that poverty is among the strongest predictors of LC since it significantly increases the risk of diagnosis at a higher age, or later stage, as well as the rapid increase in multiple morbidities [12,15,36]. Furthermore, economic deprivation may limit access to and utilization of continuous and high-quality medical care and, therefore, increase the risk of lower survival [37].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, a study in Romania (12) revealed a significantly higher percentage of patients diagnosed with late-stage breast cancer during the country's economic crisis compared to the previous interval (56.3% vs. 46.9%). These findings are in accordance with the international literature, which supports that poverty is among the strongest predictors of LC since it significantly increases the risk of diagnosis at a higher age, or later stage, as well as the rapid increase in multiple morbidities [12,15,36]. Furthermore, economic deprivation may limit access to and utilization of continuous and high-quality medical care and, therefore, increase the risk of lower survival [37].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, there is a lack of consistency between different individual and country level health impact findings [11]. Cancer is among the chronic diseases that tend to be affected 2 of 10 during recession periods [12][13][14][15]. Lung cancer (LC) in particular is the most common example of disease-specific rates that present increasing trends in population groups living in austerity [16].…”
Section: Introductionmentioning
confidence: 99%
“…The study incorporated a comprehensive analysis of variables that extended to patients' demographics and medical history, alongside specific characteristics pertinent to urothelial cancer and cancer management data [32][33][34]. These encompassed patients' age, sex, body mass index, history of substance use, referral form, COVID-19 vaccination status, number of comorbidities, tumoral grading, and duration of hospitalization.…”
Section: Variablesmentioning
confidence: 99%
“…The COVID-19 pandemic, an unprecedented global health crisis, reshaped various dimensions of society, from healthcare systems to educational infrastructures [1][2][3][4]. A prominent transition instigated by this crisis was the abrupt shift to remote learning, attempting to curb the spread of the virus while maintaining educational processes.…”
Section: Introductionmentioning
confidence: 99%